The Effects of Microplastics and Additives on Ecosystem Function, Structure, and Signaling - Sally Gaw; Maia Raymundo; Ciemon F. Caballes (Global Change Biology, 2026)
Microplastics (MPs) and their associated chemical additives are pervasive contaminants whose ecological impacts extend beyond organismal toxicity to fundamentally alter ecosystem processes. We synthesize current understanding of how MPs affect three interconnected dimensions of ecosystem integrity: ecosystem structure, ecosystem function, and ecosystem signaling. Across terrestrial, freshwater, and marine ecosystems, MPs alter biodiversity, community composition, trophic interactions, and habitat complexity, driving cascading changes in food‐web architecture. They also impair key ecosystem functions, including primary production, decomposition, nutrient and carbon cycling, bioturbation, filtration, and energy transfer, with consequences for ecosystem productivity and resilience. We further identify ecosystem signaling as an emerging but underappreciated dimension of plastic pollution. MPs and their additives disrupt chemical, microbial, and sensory communication by altering semiochemicals, pheromones, quorum sensing, predator–prey recognition, host–microbiome interactions, and plant–soil feedbacks, thereby modifying behaviors and ecological processes that regulate ecosystem dynamics. Climate change further amplifies these effects through warming, altered hydrology, hypoxia, ocean acidification, ultraviolet radiation, and extreme weather events, which increase plastic fragmentation, additive release, bioavailability, and organismal susceptibility. We propose an integrated conceptual framework linking structural, functional, and signaling pathways to explain how MPs reshape ecosystem resilience under global change. Recognizing ecosystem signaling alongside ecosystem structure and function provides a more comprehensive framework for predicting ecosystem responses and identifying priorities for future research, conservation, and environmental management.